Causes and mechanisms of synchronous succession trajectories in primeval Central European mixed Fagus sylvatica forests. (25th January 2019) - Rey, Fabian; Gobet, Erika; Schwörer, Christoph; Wey, Othmar; Hafner, Albert; Tinner, Willy
Abstract: Natural succession trajectories of Central European forest ecosystems are poorly understood due to the absence of long‐term observations and the pervasive effects of past human impacts on today's vegetation communities. This knowledge gap is significant given that currently forest ecosystems are expanding in Europe as a consequence of global change. Annually laminated sediments were extracted from two small lowland lakes (Moossee 521 m a.s.l.; Burgäschisee 465 m a.s.l.) on the Swiss Plateau. We combine high‐resolution palaeoecological and quantitative analyses to assess changes in vegetation during the Neolithic. We test for regionally synchronous land‐use phases and plant successional patterns that may originate from complex interactions between human and climatic impacts. Mixed Fagus sylvatica forests dominated the Swiss Plateau vegetation over millennia. During the period 6, 500–4, 200 cal yearbp, pronounced forest disruptions accompanied by increased fire and agricultural activities occurred at c . 6, 400–6, 000 cal yearbp, 5, 750–5, 550 cal yearbp, around 5, 400 cal yearbp and at 5, 100–4, 600 cal yearbp . Biodiversity increased during these land‐use phases, likely in response to the creation of new open habitats. After decades to centuries of land‐use, arboreal vegetation re‐expanded. In a first succession stage, heliophilous Corylus avellana shrubs were replaced by pioneer Betula trees. These open arboreal communities were out‐competed within 150–200 years by late‐successional F. sylvatica and Abies alba forests. Most strikingly, cross‐correlations show that these successions occurred synchronously (±11 years) and repeatedly over large areas (>1, 000 km 2 ) and millennia. Synthesis . First notable human impact shaped the primeval mixed Fagus sylvatica forests in Central Europe from c . 6, 800–6, 500 cal yearbp on. Agrarian societies were susceptible to climate changes and we hypothesize that climate‐induced, simultaneous agricultural expansion and contraction phases resulted in synchronous regional forest successions. Currently, forests are expanding in Central Europe as a result of land abandonment in marginal areas. Our results imply that mixed Fagus sylvatica forests with Abies alba and Quercus may re‐expand rapidly in these areas, if climate conditions will remain within the range of the mid‐Holocene climatic variability (with summers c . +1–2°C warmer than today). Abstract : First notable human impact shaped the primeval mixed Fagus sylvatica forests in Central Europe from c . 6, 800–6, 500 cal yearBP on. Agrarian societies were susceptible to climate changes and we hypothesize that climate‐induced, simultaneous agricultural expansion and contraction phases resulted in synchronous regional forest successions over millennia.